Lutein and Zeaxanthin in the Lipid Bilayer–Similarities and Differences Revealed by Computational Studies - Makuch, Krzysztof; Hryc, Jakub; Markiewicz, Michal; Pasenkiewicz-Gierula, Marta (Frontiers in Molecular Biosciences, 2021)
Lutein and zeaxanthin are two similar carotenoids of the xanthophyll subgroup. Carotenoids are synthesized almost entirely by plants but are also present in significant amounts in animals. They are essential components of the lipid matrix of biomembranes, and one of their functions is to protect cells from light radiation, free radicals and oxidative stress. Carotenoids, depending on their chemical structure, can locate at various positions and in different orientations in the bilayer. Xanthophylls (XAN) are polar and in the bilayer are positionally restricted. In the case of lutein and zeaxanthin, whose both ionone rings are hydroxy-substituted and as such are anchored in the lipid bilayer interfaces, the position is generally transmembrane. However, both experimental and computer modelling studies indicate that lutein can also locate horizontally below the bilayer interface. This location has never been observed for zeaxanthin. To find a molecular-level explanation for the difference in the orientations of the XAN molecules in the bilayer, a number of phosphatidylcholine-XAN bilayers were constructed and molecular dynamics (MD) simulated for 1.1 µs each. The all-trans XAN molecules were initially placed either parallel or perpendicular to the bilayer surface. With the exception of one lutein, the horizontally placed molecules adopted the transmembrane orientation within 100-600 ns. On the basis of detailed analyses of the XAN orientations and the numbers and lifetimes of their interactions in the bilayer, a plausible explanation is offered as to why a lutein molecule may remain in the horizontal orientation while zeaxanthin does not. Contrary to common believe, lutein horizontal orientation is not related to the ε-ring rotation around the C6′-C7′ bond.